2012
DOI: 10.1177/0148607112464238
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐abdominal Pressure as a Prognostic Factor for Tolerance of Enteral Nutrition in Critical Patients

Abstract: In critically ill patients, there is a relation between IAP values and the tolerance of EN. The baseline IAP with the APACHE II score can predict the tolerance of EN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…The authors proposed an interesting combination of IAP and APACHE II score in order to predict FI. Indeed, the results suggest that patients with higher APACHE II scores are more vulnerable to IAP induced FI [114]. In many other studies, higher severity of illness scores have been reported in patients with IAH, as well as in patients with GI dysfunction and FI [4,19,20].…”
Section: Studies Connecting Iap and Clinical Symptoms Of Gi Dysfunctionmentioning
confidence: 70%
See 2 more Smart Citations
“…The authors proposed an interesting combination of IAP and APACHE II score in order to predict FI. Indeed, the results suggest that patients with higher APACHE II scores are more vulnerable to IAP induced FI [114]. In many other studies, higher severity of illness scores have been reported in patients with IAH, as well as in patients with GI dysfunction and FI [4,19,20].…”
Section: Studies Connecting Iap and Clinical Symptoms Of Gi Dysfunctionmentioning
confidence: 70%
“…A higher prevalence of feeding intolerance (FI) in patients with IAH has been demonstrated in several studies [4,114]. Bejarano et al [114] showed that baseline IAP together with an APACHE II score may predict FI.…”
Section: Studies Connecting Iap and Clinical Symptoms Of Gi Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bejarano et al [30] assessed the relationship between baseline IAP (before starting EN) and EN tolerance. According to their findings, APACHE II scores combined with IAP served to predict a patient’s EN tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the criteria for intolerance were not the same. In the study by Bejarano et al [30] a GRV > 200 mL was already considered as intolerance; patients in their study with an IAP of 14 mmHg before EN started had a high risk of EN intolerance if their APACHE II was above 14. In our study, this IAP value of 14 mmHg was found to be the best cut-off point for predicting EN intolerance.…”
Section: Discussionmentioning
confidence: 99%